Operation Observant Compass and the Hunt for Joseph Kony: The Use of Special Operations Forces in Humanitarian Interventions - Moriarty, Daniel (Scientia Militaria - South African Journal of Military Studies, 2024)
Operation Observant Compass, the United States 2011–2017 military intervention in Central Africa to defeat Joseph Kony’s Lord’s Resistance Army, offers several lessons for students and practitioners of military geography. As opposed to previous humanitarian interventions, Operation Observant Compass featured a notably small force of roughly 100 special operations forces and support personnel. This special operations forces element, deployed to the tri-border region between the Democratic Republic of the Congo, South Sudan, and the Central African Republic, confronted an elusive enemy force in an operational area roughly 200 000 square kilometres in size. Using a mixed-methods approach, the study, on which this article is based, argued that Operation Observant Compass resulted in a net positive humanitarian outcome despite failing to kill or capture Kony. First, using datasets on Lord’s Resistance Army attacks and Operation Observant Compass troop positions, this article presents a geospatial analysis of potential deterrence effects created by the deployment of special operations forces, such as the United States Special Forces or “Green Berets”. Second, using primary research conducted by the former psychological operations commander of Operation Observant Compass and the Ugandan People’s Defence Force counterpart, analysis is presented on the efficacy of psychological operations campaigns that sought to weaken the Lord’s Resistance Army through defections to regional security forces. The study also considered ancillary effects received through United States military medical personnel deployed in support of special operations forces, as well as a counterfactual argument in which United States forces were not directly deployed into the tri-border region. This article contributes to the existing literature by expanding understanding of a little-studied chapter in foreign military deployments in sub-Saharan Africa, considering the nexus between use of special operations forces and humanitarian interventions. Methodologically, the use of a geographic information system argues for a consideration of geographical proximity between forces in creating a deterrent effect in “low-intensity” or irregular conflicts.